Predictors of surgical outcome among patients with spontaneous supratentorial intracerebral hemorrhage: A prospective single institutional study - Lamichhane, Somraj; Devbhandari, Ruchi; Tripathee, Sabin; Chapagain, Manisha (Nepal Journal of Neuroscience, 2021)
Introduction: Intracerebral hemorrhage (ICH) is a potentially devastating neurologic emergency with long-term functional independence achieved in only limited patients with good prognostic factors. The objective of this study is toidentify the predictors of functional outcome in terms of modified Rankin Scale (mRS) following craniotomy and evacuation of spontaneous supratentorial ICH. Methodology: It is a prospective study of forty patients conducted at the College of Medical Sciences (CMS) from May 2019 to April 2020 with three months follow-up. Patients of spontaneous supratentorial ICH with features of raised ICP and deteriorating GCS underwent surgical evacuation. The various predictors of outcome like Glasgow Coma Score (GCS) and pupillary inequality at presentation, age, location of hematoma, clot volume, comorbidities, intra-ventricular extension and involvement of dominant hemisphere were documented and compared with outcome in terms of modified Rankin Scale (mRS). Results: The mortality rate at three months was 25% (32% in deep seated and 13.3% in lobar ICH) and higher in patients with poor GCS and pupillary inequality at presentation, volume >100 ml, intra-ventricular extension and patients undergoing decompressive craniectomy. Twenty patients (50%) had a favorable outcome (mRS 1-3) at follow-up, while 20 (50%) had a poor outcome (mRS 4-6). Unfavorable outcome was significantly higher among deep seated hematoma, age>70 years, poor GCS and pupillary inequality at presentation, clot volume >100ml, pre-existing co-morbidity, patients undergoing decompressive craniectomy and involvement of dominant hemisphere. Conclusion: Surgical evacuation of spontaneous supratentorial ICH is associated with high mortality in patients with poor GCS and pupillary inequality at presentation, and large clot volume with intraventricular extension. However, young patients with good pre-morbid status, moderate volume of hematoma, not involving dominant hemisphere and moderate to good GCS have good functional outcome.